Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Florida red tides and adverse birth outcomes: Investigating harmful algae as a novel environmental exposure - Rain E. Freeman; Quynh Anh Nguyen; Sandy Haaf; Jason L. Salemi; Catherine M. Bulka (Chemosphere, 2025)

Adolescent and Young Adult Social Media Food Marketing Exposure: Influence of Eating Behavior Traits on Brand Recall, Craving, and Purchase - Sara Maksi; Kathleen Keller; Frank Dardis; Jason Freeman; Martina Vecchi; Travis Masterson (Journal of Nutrition Education and Behavior, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Comprehensive safety assessment of serendipity berry sweet protein produced from Komagataella phaffii - Elaine L. Freeman; Rachel Ward; Mary M. Murphy; Tina Wang; Jason Ryder (Regulatory Toxicology and Pharmacology, 2024)

Knockdown of the Non-canonical Wnt Gene Prickle2 Leads to Cerebellar Purkinje Cell Abnormalities While Cerebellar-Mediated Behaviors Remain Intact - Parker W. Abbott; Jason B. Hardie; Kyle P. Walsh; Aaron J. Nessler; Sean J. Farley; John H. Freeman; John A. Wemmie; Linder Wendt; Young-cho Kim; Levi P. Sowers; Krystal L. Parker (The Cerebellum, 2024)

Modeling identifies variability in SARS-CoV-2 uptake and eclipse phase by infected cells as principal drivers of extreme variability in nasal viral load in the 48 h post infection - Jason Pearson; Timothy Wessler; Alex Chen; Richard C. Boucher; Ronit Freeman; Samuel K. Lai; Raymond Pickles; M. Gregory Forest (Journal of Theoretical Biology, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Clinical withdrawal symptom profile of synthetic cannabinoid receptor agonists and comparison of effects with high potency cannabis - Sam Craft; Jason A. Ferris; Monica J. Barratt; Larissa J. Maier; Michael T. Lynskey; Adam R. Winstock; Tom P. Freeman (Psychopharmacology, 2022)
Synthetic cannabinoid receptor agonists (SCRAs) may be used as an alternative to natural cannabis; however, they may carry a greater risk of problematic use and withdrawal. This study aimed to characterise the withdrawal symptom profile of SCRAs and compare their profile of effect with high-potency herbal cannabis. Global Drug Survey data (2015 and 2016) were used to access a clinically relevant sample of people reporting use of SCRAs >10 times in the past 12-months, a previous SCRA quit attempt, and lifetime use of high-potency herbal cannabis. Participants completed an 11-item SCRA withdrawal symptom checklist and compared SCRAs and high-potency herbal cannabis on their onset and duration of effects, speed of the development of tolerance, severity of withdrawal, and difficulty with dose titration. Participants ( n = 284) reported experiencing a mean of 4.4 (95% CI: 4.1, 4.8) withdrawal symptoms after not using SCRAs for >1 day; most frequently reported were sleep issues (59.2%), irritability (55.6%), and low mood (54.2%). Withdrawal symptoms were significantly associated with frequency (>51 vs. 11–50 times per year: IRR = 1.43, 95% CI: 1.16, 1.77, p = 0.005) and quantity (grams per session: IRR = 1.13, 95% CI: 1.05, 1.22, p = 0.001) of SCRA use. Compared to high-potency herbal cannabis, SCRAs were rated as having a faster onset and shorter duration of effects, faster development of tolerance, and more severe withdrawal ( p ’s < 0.001). In conclusion, SCRA withdrawal symptoms are more likely to occur after greater SCRA exposure. The effects of SCRA indicate a more severe withdrawal syndrome and a greater risk of problematic use than natural cannabis.

The impact of climate change on mediterranean intertidal communities: losses in coastal ecosystem integrity and services - Gianluca Sarà; Martina Milanese; Ivana Prusina; Antonio Sarà; Dror L. Angel; Branko Glamuzina; Tali Nitzan; Shirra Freeman; Alessandro Rinaldi; Valeria Palmeri; Valeria Montalto; Marco Lo Martire; et al. (Regional Environmental Change, 2014)

The effects of chronic nitrogen fertilization on alpine tundra soil microbial communities: implications for carbon and nitrogen cycling - Diana R. Nemergut; Alan R. Townsend; Sarah R. Sattin; Kristen R. Freeman; Noah Fierer; Jason C. Neff; William D. Bowman; Christopher W. Schadt; Michael N. Weintraub; Steven K. Schmidt (Environmental Microbiology, 2008)
Summary Many studies have shown that changes in nitrogen (N) availability affect primary productivity in a variety of terrestrial systems, but less is known about the effects of the changing N cycle on soil organic matter (SOM) decomposition. We used a variety of techniques to examine the effects of chronic N amendments on SOM chemistry and microbial community structure and function in an alpine tundra soil. We collected surface soil (0–5 cm) samples from five control and five long‐term N‐amended plots established and maintained at the Niwot Ridge Long‐term Ecological Research (LTER) site. Samples were bulked by treatment and all analyses were conducted on composite samples. The fungal community shifted in response to N amendments, with a decrease in the relative abundance of basidiomycetes. Bacterial community composition also shifted in the fertilized soil, with increases in the relative abundance of sequences related to the Bacteroidetes and Gemmatimonadetes , and decreases in the relative abundance of the Verrucomicrobia . We did not uncover any bacterial sequences that were closely related to known nitrifiers in either soil, but sequences related to archaeal nitrifiers were found in control soils. The ratio of fungi to bacteria did not change in the N‐amended soils, but the ratio of archaea to bacteria dropped from 20% to less than 1% in the N‐amended plots. Comparisons of aliphatic and aromatic carbon compounds, two broad categories of soil carbon compounds, revealed no between treatment differences. However, G‐lignins were found in higher relative abundance in the fertilized soils, while proteins were detected in lower relative abundance. Finally, the activities of two soil enzymes involved in N cycling changed in response to chronic N amendments. These results suggest that chronic N fertilization induces significant shifts in soil carbon dynamics that correspond to shifts in microbial community structure and function.

The self-incompatibility locus (S) and quantitative trait loci for self-pollination and seed dormancy in sunflower - Sonali D. Gandhi; Adam F. Heesacker; Carrie A. Freeman; Jason Argyris; Kent Bradford; Steven J. Knapp (Theoretical and Applied Genetics, 2005)